South Korean Science and Technology Policy - V. G. Samsonova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2021)
The article analyzes the policy of South Korea in the field of science and technology, examines the main trends of the ROK’s science development, current state, key problems and prospects of the industry. The characteristics of the state scientific and technological policy and its main actors are presented. It is stated that at the beginning South Korea abundantly used adopt experience, foreign technologies and successfully got accepted them in production. The ROK succeeded to hold leading positions in the world innovation ratings through smart patent activity, essential investment and government policy. At the same time, the author predicts the necessity of tremendous efforts, includes but not limited to fi ancial injection for maintaining such high figure. The issue of not only human resources’ import but also keeping of South Korean skilled labor, the demand and competition for whom are ramping up dramatically, has still unresolved. The article focuses on the impact of the Covid-19 pandemic on the scientific policy and the development of innovations in the fight against such pandemics. It was revealed that research in the field of biotechnology and establishment of “smart” health care centers based on the innovations become a priority of science policy. It was noted that South Korea one of the first reaps the benefits of IT solution, which helps to prevent economics collapse and further viral shedding through the rapid digital technics’ implementing.